Dual‐Band‐Tunable White‐Light Emission from Bi3+/Te4+ Emitters in Perovskite‐Derivative Cs2SnCl6 Microcrystals. (18th January 2022) - Zhang, Wei; Zheng, Wei; Li, Lingyun; Huang, Ping; Gong, Zhongliang; Zhou, Ziwei; Sun, Jinyue; Yu, Yan; Chen, Xueyuan
Abstract: Luminescent metal halides have attracted considerable attention in next‐generation solid‐state lighting because of their superior optical properties and easy solution processibility. Herein, we report a new class of highly efficient and dual‐band‐tunable white‐light emitters based on Bi 3+ /Te 4+ co‐doped perovskite derivative Cs2 SnCl6 microcrystals. Owing to the strong electron‐phonon coupling and efficient energy transfer from Bi 3+ to Te 4+, the microcrystals exhibited broad dual‐band white‐light emission originating from the inter‐configurational 3 P0, 1 → 1 S0 transitions of Bi 3+ and Te 4+, with good stability and a high photoluminescence (PL) quantum yield of up to 68.3 %. Specifically, a remarkable transition in Bi 3+ ‐PL lifetime from milliseconds at 10 K to microseconds at 300 K was observed, as solid evidence for the isolated Bi 3+ emission. These findings provide not only new insights into the excited‐state dynamics of Bi 3+ and Te 4+ in Cs2 SnCl6, but also a general approach to achieve single‐composition white‐light emitters based on lead‐free metal halides through ns 2 ‐metal ion co‐doping. Abstract : A strategy based on Bi 3+ /Te 4+ co‐doping was developed to achieve dual‐band‐tunable white‐light emission in perovskite‐derivative Cs2 SnCl6 microcrystals with a quantum yield of up to 68.3 %. Solid evidence including the transition in photoluminescence lifetime from milliseconds at 10 K to microseconds at 300 K was provided to unravel the photoluminescence originating from the inter‐configurational 3 P0, 1 → 1 S0 transitions of Bi 3+ /Te 4+ .